INTERNAL FUNDING AND OTHER FACTORS AFFECTING THE DEBT POLICY OF MINING COMPANIES - Anggono, Jelena; Viriany, Viriany (International Journal of Application on Economics and Business, 2025)
Mining companies play a pivotal role in Indonesia’s economy, given their substantial presence within the stock exchange, comprising approximately 20% of the total listed companies on the Indonesia Stock Exchange. The mining sector’s capital-intensive nature presents challenges in deciding financing solutions for its operations. The critical decision regarding debt policies will affect the company’s future whether the company is using their internal funding or taking on an external debt. This study consists of five independent variables, namely X1 asset structure (tangibility), X2 liquidity, X3 internal funding, X4 profitability, and X5 company size, with the dependent variable (Y) debt policy. The objective of this research is to determine whether asset structure, liquidity, internal funding, profitability, and company size affect the debt policy of mining companies listed on the Indonesia Stock Exchange in the 2018-2022 period. The result of the research provides insights regarding the types of relationship between these financial factors and debt policy. The sample was selected using a purposive sampling method and with total data passed 160 datas. Data analysis was performed using a processing tool, namely the Statistical Package for Social Sciences (SPSS) version 25, as well as the multiple linear regression, F-test, T-test and adjusted R2 test. The results showed that the asset structure variable and company size variable have a significant positive effect on corporate debt policy variable. Liquidity and internal funding variables have a significant negative effect on debt policy. Surprisingly, the profitability variable has no effect on debt policy. This means that mining companies with more tangible assets and larger sizes are more inclined to use debt as a financing strategy, while those with higher liquidity and internal funding tend to rely less on external debt.